The usefulness of C-reactive protein and neutrophil-to-lymphocyte ratio for predicting the outcome in hospitalized patients with liver cirrhosis. Issue 1 (December 2015) - Kwon, Jung; Jang, Jeong; Kim, Young; Lee, Sung; Nam, Soon; Jaegal, Dongwook; Lee, Seungok; Bae, Si
Abstract Background The role of clinical parameters such as systemic inflammatory response syndrome (SIRS) criteria in predicting the infection remains unclear in cirrhosis patients. The aim was to evaluate the usefulness of inflammatory markers including C-reactive protein (CRP) and the neutrophil-to-lymphocyte ratio (NLR) for diagnosis of infection and predicting the outcomes in hospitalized cirrhotic patients. Methods The study included 184 cirrhotic patients consecutively hospitalized from 2011 to 2012. The presence of overt infection and survival was evaluated. CRP concentration, NLR, Model for End-Stage Liver Disease (MELD) score and the presence of SIRS were assessed. Results The main cause of admission was uncontrolled ascites (36.4 %), followed by varix bleeding (23.9 %), and hepatic encephalopathy (13.6 %). Fifty-eight patients (31.5 %) had overt infection during hospitalization and thirty-two patients (17.4 %) expired during the follow up period (median 38 months). Ninety-two patients (52.2 %) fulfilled the SIRS criteria and among them, only 32 patients (38.5 %) had the overt infection. For diagnose of the infection, baseline CRP concentration was a significant factor compared to the presence of SIRS (odds ratio 1.202, P  = 0.003). For predicting one-month short-term survival, MELD score, NLR and WBC count were significant factors but in Child-Pugh class C patients, NLR was only an independent factor. Conclusions CRP was a significant indicator of infection in hospitalized cirrhotic patients and a NLR was a useful predictor of 1-month survival, particularly in Child–Pugh class C patients. This study suggests that the inflammatory markers such as CRP and NLR can help identify cirrhotic patients at risk of unfavorable outcomes.